The influence of intellectual capital and corporate governance on financial performance of Islamic banks - Rifqi Muhammad; Muhammad Aldino Mangawing; Selfira Salsabilla (Faculty of Economics, Universitas Islam Indonesia, 2021)
Purpose - This study aims to analyze the effect of intellectual capital, independent directors, academic directors, and sharia supervisory boards on the financial performance of Islamic banks. The selection of samples observation based on the database of Best Islamic Financial Institutions Award, includes Afghanistan, Algeria, Bahrain, Bangladesh, Brunei Darussalam, Egypt, Indonesia, Jordan, Kazakhstan, Kuwait, Lebanon, Malaysia, Maroko, Nigeria, Oman, Pakistan, Palestine, Qatar, Saudi Arabia, Singapore, South Africa, Sri Lanka, Thailand, Tunisia, Turkey, and Uni Emirate Arab. Methodology - This study uses a sample of 20 Islamic banks in several countries which received the